Qualitatively beyond the ledger: unravelling the interplay of organisational control, whistleblowing systems, fraud awareness, and religiosity - Ach Maulidi; Muhammad Wisnu Girindratama; Anton Robiansyah Putra; Rida Perwita Sari; Dian Anita Nuswantara (Cogent Social Sciences, 2024)
This study endeavours to qualitatively examine the intricate interplay between organisational control, whistleblowing systems, fraud awareness, and religiosity from the unique perspective of internal auditors. We interviewed the state internal auditors of the Republic of Indonesia, including the inspectorate departments. We had fifteen informants participating in our study. The data confirm our theoretical framework. According to our proposed preventive measures (organisational control, whistleblowing system, fraud awareness and religiosity aspects), organisational control plays more significant role than others. We cannot claim that others are unimportant measures in preventing fraud. However, our study documents that other preventive aspects become complementary measures to enhance the effectiveness of organisational control. By viewing from a broad sense, those proposed preventive measures operate interactionist basis. This study is unique in its analysis as this study is the first study that qualitatively observes the interactions of organisational control, whistleblowing system, fraud awareness and religiosity aspects to prevent fraud. Our study contributes to fraud prevention literature. To date, we lack theoretical literature on the interactions of organisational control, whistleblowing system, fraud awareness and religiosity aspects to prevent fraud. Most of the prior studies examine those constructs in isolation from one another.